BUSINESS GAMES AS THE FORM OF ENDOWED CHILDREN PREPARATION TO RESEARCH ACTIVITY - N.I. Polikhun; M.A. Popova (Kherson State University, 2010)
Modern computer business games using IT technologies provide numerous opportunities for improving ecological training of endowed children to research activities, including not only theoretical training but also the acquisition of practical skills.